New Tendencies in Project Management - Kogotkova, Irina; Guseva, Maria; Brikoshina, Irina; Soroko, Grigory; Chernova, Aleksandra; Chernova, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the results of research, the objective of which was to determine the prospects for developing project competencies of organizations and project team members in accordance with new tendencies in project management. The nature of projects is such that the project participants in the course of elaboration and fulfillment thereof should identify and master new knowledge and search for new solutions. It is not always that the acquired knowledge and project competencies take into account the trends of development in this management sphere. This discrepancy determined the research problem. The research results can make up for the insufficient coverage of the problem in scientific literature and focus the supervisors in their practical activity on generating project competencies in accordance with the prevailing development vectors. The methods and main research tools include content analysis, expert assessments, generalization, and classification. As a result of research, there were revealed novations in global tendencies of project management that will influence the generation of new project competencies, such as new roles of project managers and the development of flexible personal skills, elaboration of hybrid project management methods, digitalization of project communications, artificial and emotional intelligence, and some others.